The stripping of the altars : traditional religion in England, c.1400-c.1580 - Duffy, Eamon (New Haven ; London : Yale University Press, 2005)
"This profoundly influential book re-examines events leading up to the Reformation and enriches our understanding of the period. It recreates lay people's experience of religion in the pre-Reformation church showing that late medieval Catholicism was neither decadent nor decayed, but was a strong and vigorous tradition, and that the Reformation represented a violent rupture from a popular and theologically respectable religious system. For this edition, Duffy has written a substantial new introduction, including a discussion of the Lollards and reflections on recent developments in Reformation studies."--Jacket
pt. I: The structures of traditional religion. A. Liturgy, learning and the laity. Seasons and signs: the liturgical year ; How the plowman learned his Paternoster. B. Encountering the holy. The mass ; Corporate Christians ; The saints. C. Prayers and spells. "Lewed and learned": the laity and the primers ; The devotions of the primers ; Charms, pardons and promises: lay piety and "superstition" in the primers. D. Now, and at the hour of our death. Last things ; The pains of Purgatory. -- pt. II: The stripping of the altars, 1530-1580. The attack on traditional religion I: From the break with Rome to the Act of Six Articles ; The attack on traditional religion II: To the death of Henry VIII ; The attack on traditional religion III: The reign of Edward VI ; The impact of reform: Parishes ; The impact of reform: Wills ; Mary ; Elizabeth
Previous edition: 1992
Includes bibliographical references (pages 595-625) and index
Keywords: Catholic Church -- England -- Customs and practices; Church of England -- Customs and practices; Reformation -- England; Anglican Communion -- England -- History -- 16th century; England -- Religious life and customs; England -- Church history -- 16th century